PENGARUH PEMBERIAN ABU SEKAM SEBAGAI SUMBER SILIKA (SI) BAGI PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oriza sativa l.) - Teguh Budi Prasetyo; Irwan Darfis; Rahmi Fitri (Jurnal Solum, 2008)
This research was conducted in greenhouse at Agriculture Faculty of Andalas University from August 2006 to February 2007.  The objective of the research was to study  the effect of fly ash as silicon (Si) resource for plant growth and rice production.  The experiment was designed on Completely Randomized Block Design in four treatments and three replicates.  The treatments consisted of without fly ash, 1400 kg/ha, 2800 kg/ha and 5600 kg/ha fly ash.  The results showed that fly ash could increase available fosfor, silica, cations and reduce Aluminium of the soil.  Fly ash could also increase production and absorbtion of fosfor and plant silicon.Key words :  Fly ash, silicon, and rice production